ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REAKSI INVESTOR DI SEKITAR PENGUMUMAN RIGHT ISSUE STUDI EMPIRIS DI BURSA EFEK JAKARTA - Djoko Widagdo (Jurnal Manajemen Dirgantara, 2015)
This study is examined whether a right issues announcement in Indonesian money market giving an influence to stock price that calculated from abnormal return around announcement stock day. In addition to that, this study test on whether company size, offer price and price to book value influence investor reaction to the right issue announcement. The samples of this study are companies who done right issues in Jakarta Stock Exchange during 1992 to 1996, where event date is a reference. Event study used in this research. Using one sample t test, the result shows that stock price arise before right issue announcement and fall down after it, then start arise over again. Market or investor on the whole are react positively to right issue announcement. The regression outcome shows negative correlation between abnormal return and company size; means small company will have higher return compare to bigger one. There is also positive correlation between abnormal return and offerprice of new stock. So that offer price gives positive signaling effect to abnormal return stock at the right issue announcement. Lower offer price will cause bigger decreasing price and vice versa. This study also indicates positive correlation between abnormal return and size of growth. It means companies with low book to market (High PBV) are more profitable than companies with high book to market (Low PBV).